Preparation of α-l-Rhamnobiosides by Open and Conventional Glycosylations for Studies of the rHPL Lectin - Demeter, Fruzsina; Balogh, Tímea; Fu, Tse-Kai; Chang, Margaret Dah-Tsyr; Lee, Yuan-Chuan; Borbás, Anikó; Herczeg, Mihály (Synlett, 2019)
To study the effect of oligosaccharides on biological systems (e.g., carbohydrate–lectin interactions), chemical synthesis of the desired carbohydrate derivatives is highly desirable, but it is usually a very complicated task. Most of the stereo- and regioselective glycosylation reactions are carried out by using protected acceptors and donors. At the same time, open glycosylation (use of an unprotected acceptor) may shorten the reaction pathway, if sufficient selectivity can be achieved between the acceptor hydroxyl groups. Toward synthesis of higher oligomers and multivalent derivatives, which are often useful for lectin binding studies, open glycosylation reactions of propargyl and phenylthio rhamnosides were investigated as a rapid route to the α-(1,3)-linked rhamnobioside binding motif. The efficacy of open glycosylations proved to be highly dependent on both the type of donor and the solvent applied. Using a trichloroacetimidate donor in 1,4-dioxane, the open glycosylation reactions proceeded with high regioselectivity and in good yields. Conventional glycosylations, on the other hand, afforded the α-(1,2)- and α-(1,3)-linked rhamnobioside derivatives with slightly higher yields via three-step longer syntheses.
Keywords: rhamnobioside; trichloroacetimidate; thioglycoside; regioselective; stereoselective; glycosylation